Pengaruh Youtube dan Media Sosial Facebook Terhadap Ekonomi Politik Komunikasi - anna kurniawati (KOMUNIDA : Media Komunikasi dan Dakwah, 2021)
This research wants to know the influence of Youtube and Fcaebook on the political economy of communication. This studi uses the political economy theory of communication and new media theory. This study uses a qualitative methololody with a literature revies study. Based on th theory of new media and the political economy of communication, global captalism based on digital technology and the internet has transformed into e-capitalism that dominates the global media market. Facebook indireclty has hires its users to generate capital accumulation without them knowing that they have become “workers”. Basically, the activity of uploading videos oh Youtube can be classified as political economy activity. This is because in the proces of production, distribution and consumption of media content, it is the company that retains the highest authority. Users are able to produce and distribute ther content through the platforms provided, but users need to obey the rules that have been made by the company. This is done to increase the company’s profit. The existence of new media such as Youtube has made the audience good consumers and has prepared them to become obedient workers to the owners of capital.